2022
DOI: 10.1111/jre.12993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of titanium dioxide microparticles and nanoparticles on cytoskeletal organization, cell adhesion, migration, and proliferation in human gingival fibroblasts in the presence of lipopolysaccharide

Abstract: Background and objective: Titanium wear particles may participate in the etiology of peri-implantitis. However, the influence of titanium wear particles on biological behavior of human gingival fibroblasts (HGFs) in the presence of LPS is still not clear.The present study demonstrated the effects of titanium dioxide micro-and nanoparticles (TiO 2 MPs and NPs) on HGF cell viability, cytoskeletal organization, adhesion, migration, and proliferation in vitro, and LPS was used to mimic the in vivo condition.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The elongated shape of Ag@TiO 2 NRs on GG hydrogel film improved cell adhesion, which aided cell proliferation [48,49]. Researchers have widely reported TiO 2 's beneficial effect on cellular functions such as cell adhesion and proliferation [50,51]. In addition, it is commonly known that TiO 2 nanomaterials, including TiO 2 nanorods, are biologically inert and nontoxic to both human and animal cells [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…The elongated shape of Ag@TiO 2 NRs on GG hydrogel film improved cell adhesion, which aided cell proliferation [48,49]. Researchers have widely reported TiO 2 's beneficial effect on cellular functions such as cell adhesion and proliferation [50,51]. In addition, it is commonly known that TiO 2 nanomaterials, including TiO 2 nanorods, are biologically inert and nontoxic to both human and animal cells [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…The actin-binding protein vinculin is vital in regulating cell adhesion and is a reliable indicator of this process. Figure C shows the images of the immunofluorescence staining results, and Figure D shows the results of the fluorescence quantification of vinculin. The results showed that the cells exhibited a more spread morphology and stronger expression of actin stress fibers on the Col-5BG and Col-7BG membranes, which also had a higher vinculin expression.…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancies in inflammation marker gene expression levels mentioned above between periodontitis and peri-implantitis fibroblasts might be explained by the lack of attachment apparatus around dental implants. Second, the presence of titanium wear particles might be another reason (Li et al, 2022). (fibro_2)-CXCR2 (neutro_CXCR2).…”
Section: Discussionmentioning
confidence: 99%